Intracellular Delivery: Redox‐Triggered Release of Moxifloxacin from Mesoporous Silica Nanoparticles Functionalized with Disulfide Snap‐Tops Enhances Efficacy Against Pneumonic Tularemia in Mice (Small 27/2016). Issue 27 (14th July 2016) - Lee, Bai‐Yu; Li, Zilu; Clemens, Daniel L.; Dillon, Barbara Jane; Hwang, Angela A.; Zink, Jeffrey I.; Horwitz, Marcus A.
Abstract : The drug trapping and intracellular release mechanism of redox‐responsive disulfide snap‐top mesoporous silica nanoparticles (MSN‐SS‐MXF) is depicted by J. I. Zink, M. A. Horwitz and co‐workers on page 3690. Mesoporous silica nanoparticles with antibiotic (cyan) trapped within their pores by disulfide snap‐tops are avidly ingested by macrophages. The intracellular redox potential reduces the disulfide (yellow) in the stalk (green/blue), releases the caps (orange) and frees drug to kill Francisella tularensis (green). Artwork by Bastian Ruehle.